2021
DOI: 10.3389/fgene.2021.639246
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis-Related Gene Expression Profiling Screen for Prognostic Risk Signature of Pancreatic Ductal Adenocarcinoma

Abstract: Objective: Pancreatic ductal adenocarcinoma (PDAC) is highly lethal. Although progress has been made in the treatment of PDAC, its prognosis remains unsatisfactory. This study aimed to develop novel prognostic genes related to glycolysis in PDAC and to apply these genes to new risk stratification.Methods: In this study, based on the Cancer Genome Atlas (TCGA) PAAD cohort, the expression level of glycolysis-related gene at mRNA level in PAAD and its relationship with prognosis were analyzed. Non-negative matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Previously, several valuable PDAC prognostic signatures have been constructed by using bioinformatics analysis. For example, signatures based on glycolysis, m6A, ferroptosis, immune, and extracellular vesicle predict 1-year OS for PDAC with AUC at 0.805, 0.736, 0.81, 0.755, and 0.640, respectively, which were similar to our study ( Xu et al, 2020 ; Chen et al, 2021 ; Song et al, 2021 ; Xu et al, 2021 ; Yuan et al, 2021 ). However, the number of patients included in the abovementioned studies ranged from 183 to 441 and were relatively low.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previously, several valuable PDAC prognostic signatures have been constructed by using bioinformatics analysis. For example, signatures based on glycolysis, m6A, ferroptosis, immune, and extracellular vesicle predict 1-year OS for PDAC with AUC at 0.805, 0.736, 0.81, 0.755, and 0.640, respectively, which were similar to our study ( Xu et al, 2020 ; Chen et al, 2021 ; Song et al, 2021 ; Xu et al, 2021 ; Yuan et al, 2021 ). However, the number of patients included in the abovementioned studies ranged from 183 to 441 and were relatively low.…”
Section: Discussionsupporting
confidence: 88%
“…The GSEA analysis indicated that hypoxia and glycolysis pathways were upregulated in the high-risk group. Recent studies have documented that hypoxia and glycolysis-related gene signatures were associated with tumor microenvironment and might be used to predict the prognosis of PDAC patients ( Ding et al, 2021 ; Song et al, 2021 ). Hypoxia has been considered as an indicator of the inflamed tumor microenvironment and leads to activation of tumor-promoting inflammatory responses ( Triner and Shah, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kaplan–Meier survival demonstrated that patients in the high-risk group had lower survival rates than those in the low-risk group, indicating the relatively reliable performance of the Risk Score. The Risk Score models constructed by glycolysis-related genes have been proven prognostic values in pancreatic ductal adenocarcinoma [ 46 ]. Prognostic models basing on immune-related genes have also been identified in renal papillary cell carcinoma [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationships between aging-related genes (ARGs) and prognoses as well as immune infiltrations of PAAD patients remain unclear. In previous studies, ferroptosis-related signatures ( Jiang et al, 2021 ), immune-related signatures ( Wang et al, 2020 ), and glycolysis-related signatures ( Song et al, 2021 ) have been constructed to predict the OS of PAAD patients. Therefore, in this study, our purpose was to identify molecular subtypes as well as establish a risk signature based on ARGs to predict prognoses and immune microenvironments of PAAD patients.…”
Section: Introductionmentioning
confidence: 99%